2020
DOI: 10.5771/0038-6073-2020-1-2-24
|View full text |Cite
|
Sign up to set email alerts
|

Has there been a “refugee crisis”? New insights on the recent refugee arrivals in Germany and their integration prospects

Abstract: Approximately 1.2 million refugees arrived in Germany between 2015 and 2016. The national and international public discourse surrounding the arrival of these refugees covers the full spectrum of opinions. These opinions range from sceptical assessments regarding the 2015 influx as a “refugee crisis” to optimistic appraisals considering the immigration of refugees to be a solution to demographic change and labour shortages. These views are often driven by ideology and emotions rather than grounded in evidence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 23 publications
(26 reference statements)
3
79
0
Order By: Relevance
“…At the same time, women are less likely than men to participate in these courses, especially if they have children. The lower participation rate of women is usually explained by their care responsibilities, and the lack of child care services that would allow them to attend courses (Brücker et al 2020a;Croisier et al 2019;Brücker et al 2020b;Kosyakova & Brenzel 2017). As women are the main providers of child care, men have more capacity to attend language and integration courses.…”
Section: Qualifications Acquired Abroad and In The Country Of Residencementioning
confidence: 99%
See 3 more Smart Citations
“…At the same time, women are less likely than men to participate in these courses, especially if they have children. The lower participation rate of women is usually explained by their care responsibilities, and the lack of child care services that would allow them to attend courses (Brücker et al 2020a;Croisier et al 2019;Brücker et al 2020b;Kosyakova & Brenzel 2017). As women are the main providers of child care, men have more capacity to attend language and integration courses.…”
Section: Qualifications Acquired Abroad and In The Country Of Residencementioning
confidence: 99%
“…Migrants with (mainly) co-ethnic contacts tend to find employment quickly, but these jobs are often of low quality (Kogan 2016). However, quantitative analyses have shown that although most female refugees in Germany had high levels of social network support prior to their arrival (Brücker et al 2020b), they tend to have fewer "weak ties" after their arrival. This applies to contacts with Germans, as well as with individuals from the country of origin or from other countries (Fendel & Yildiz 2020).…”
Section: Institutional Support and Social Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Germany plays a prominent role in the management of refugee 1 flows given that many of these asylum applications were submitted there (1.9 Mio of the first-time applications between 2014 and 2020; Eurostat, 2021). Compared to Germany's previous experience of receiving large inflows of refugees in the early 1990s, the current situation is different in its scale, in part because many recent refugees originate from countries with a limited return perspective, at least in the short term (Degler and Liebig, 2017;Brücker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%